The jarring road to democratic inclusion: [a comparative assessment of state-society engagements in Israel and Turkey] - Rubin, Aviad; Sarfati, Yusuf; Rubin, Aviad; Sarfati, Yusuf; Tepe, Sultan; Michaeli, Inna; Golan-Nadir, Niva; Fishman, Louis; Aslan-Akman, Canan (Lexington Books, 2016)
This edited volume brings together chapters that offer theoretically pertinent comparisons between various dimensions of Israeli and Turkish politics. Each chapter covers a different aspect of state-society interactions in both countries from a comparative perspective, including the public role of religion, political culture, women rights movements, religious education, religious movements, marriage regulation, labor market inclusion, and ethnic minorities